THE REAL PURPOSE OF THE WORK AND THE DEMOVATION OF THE HUMAN BEING - Pereira Alves, Jailsom (Revista Gênero e Interdisciplinaridade, 2021)
This article analyzes and points out, in the light of the Analytical Trilogy - idealized by the pioneer Norberto Keppe, the reasons why the work is no longer a pleasant activity to the human being. As we will see, according to Keppe, it’s at work that we spend most of our time: we give up on moments together with our family and friends for our professional growth. Therefore, it is fundamental that our work provides us with motivation and, as a consequence, feelings of happiness and satisfaction, not only professional, but mainly personal. After all, it is through it that we will realize our dreams. However, what is perceived is a very great personal dissatisfaction. The lack of interest and the human being demotivation are due to the fact that the work has become distorted in its purpose. Faced with this, it’s essential to know the essence of work for the human being, in order to change his thinking and his attitudes towards good, beautiful and happiness.